„SAB’AI SAYYOR“ DOSTONINING QORAQALPOQCHA TARJIMASI (XII-XIX boblar misolida) - Azilova, Z.G. (SCIENCE and SOCIETY, 2023)
This article provides a comparative analysis of the Navoi epic „Sabai Sayyor“ in the Karakalpak language with the studied aslat. It also highlights the number of bytes in the source text and translation and their content compatibility.